Kepastian Hukum Sertifikat Elektronik Sebagai Bukti Kepemilikan Tanah - Rahul Mukadar; Adonia Ivonne Laturette; Barzah Latupono (PATTIMURA Law Study Review, 2023)
ABSTRACT : Discusses about electronic certificates which are still a problem in making land certificates. Electronic certificates were initially not in line with the considerations of the Ministerial Regulation because in the community there were policies that reaped many cons. The land registration system based on regulations issued by the government, namely PP No. 24 of 1997 concerning Land Registration (PP 24/1997) aims to guarantee legal certainty because Thus the process of land registration must be considered properly in accordance with what is regulated by law which is the reference in the process of registering each plot of land in Indonesia. Writing with the title Legal Certainty Electronic Certificates as Proof of Land Ownership with the type of research used in this study is normative juridical, by examining legal materials in the form of primary, secondary and tertiary legal materials. The results of this study found that currently carrying out trials for the implementation of electronic land certificates it will not be applied to the general public's land, but its implementation will only be limited to State-Owned Property (BMN), State-Owned Enterprises (BUMN) assets, various companies or sectors. Large-scale private sector and for land office locations that will implement the implementation of electronic certificates in this trial phase only in certain cities. The big job now, in the transition period, is to transfer the media from conventionally stored juridical data to be converted into electronic juridical data.